2019
DOI: 10.1074/jbc.ra118.005950
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between the circadian clock and androgen signaling is required to sustain rhythmic expression of Elovl3 in mouse liver

Abstract: Edited by Qi-Qun Tang ELOVL3 is a very long-chain fatty acid elongase, and its mRNA levels display diurnal rhythmic changes exclusively in adult male mouse livers. This cyclical expression of hepatic Elovl3 is potentially controlled by the circadian clock, related hormones, and transcriptional factors. It remains unknown, however, whether the circadian clock, in conjunction with androgen signaling, functions in maintaining the rhythmic expression of Elovl3 in a sexually dimorphic manner. Under either zeitgeber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Relative gene expression was quantified using real-time quantitative PCR (qPCR). Briefly, qPCR was performed in a 20 μl reaction volume containing 10 ng of cDNA and THUNDERBIRD SYBR qPCR Mix (Toyobo) and 200 nM of specific primers using the CFX96 RT-qPCR system (Bio-Rad), according to a previously described method (Chen et al, 2019). Peaks were assessed with a melting curve analysis to ensure amplification of a single product.…”
Section: Rna Extraction Reverse Transcription Pcr and Real Time Quantitative-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative gene expression was quantified using real-time quantitative PCR (qPCR). Briefly, qPCR was performed in a 20 μl reaction volume containing 10 ng of cDNA and THUNDERBIRD SYBR qPCR Mix (Toyobo) and 200 nM of specific primers using the CFX96 RT-qPCR system (Bio-Rad), according to a previously described method (Chen et al, 2019). Peaks were assessed with a melting curve analysis to ensure amplification of a single product.…”
Section: Rna Extraction Reverse Transcription Pcr and Real Time Quantitative-pcrmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (Chao et al, 2017;Chen et al, 2019). Five-micrometer-thick sections were deparaffinized with xylene and ethanol, and then antigen retrieval was conducted by pressure cooking in a citric acid salt mixture (1.8 mM citrate and 8.2 mM Na-citrate, pH 6.0) for 15 min.…”
Section: Hematoxylin and Eosin (He) Staining And Immunohistochemistrymentioning
confidence: 99%
“…This more erratic pattern of activity could very well be related to changes in GAtreated animals' circadian rhythms as gonadectomy has been shown to alter the expression of circadian clock genes that are instrumental in regulating circadian rhythms. 40,41 Although this study did not directly assess circadian rhythms, others have reported on the importance of sex hormones in circadian rhythms and patterns. [42][43][44][45] The effect of sex hormone disruption on circadian rhythms, therefore, may be another factor to consider when developing individualized physical activity interventions in transgender individuals receiving treatment that disrupt sex hormone levels.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, patients with a lower expression of PPARGC1A in tumors had a worse prognosis [34]. ELOVL3 regulates the synthesis of fatty acid elongase, which is mainly expressed in the liver and adipose tissue of animals, and the coordination between ELOVL3 and the androgen signaling pathway [35,36]. ME1 is a product of NADPH in cancers and regulated by the typical oxidative stress response pathway.…”
Section: Discussionmentioning
confidence: 99%